Antimicrobial activities of a small molecule compound II-6s against oral streptococci. Issue 1 (1st January 2021) - Zhang, Jin; Kuang, Xinyi; Zhou, Yuanzheng; Yang, Ran; Zhou, Xuedong; Peng, Xian; Luo, Youfu; Xu, Xin
ABSTRACT: Background : The side effects of present antimicrobials like chlorhexidine (CHX) and the emergence of drug resistance necessitate the development of alternative agents to control dental caries. Aim : This study developed a novel small molecule, namely II-6s, and investigated its antimicrobial activities against common oral streptococci associated with dental caries. Methods : The susceptibility of streptococci to II-6s was evaluated by the microdilution method, time-kill assay and scanning electron microscopy. The exopolysaccharides, dead/live bacteria and bacterial composition of the II-6s-treated Streptococcus mutans / Streptococcus gordonii / Streptococcus sanguinis 3-species biofilms were analyzed by confocal laser scanning microscopy, fluorescent in situ hybridization and quantitative PCR. The anti-demineralization effect and cytotoxicity of II-6s were evaluated by transverse microradiography and CCK-8 assay, respectively. Repeated exposure of S. mutans to II-6s was performed to assess if II-6s could induce drug resistance. Results : II-6s exhibited antimicrobial activity similar to CHX against S. mutans, S. gordonii and S. sanguinis and significantly inhibited exopolysaccharides production, live bacteria and the demineralizing capability of the 3-species streptococcal biofilms. Besides, II-6s showed reduced cytotoxicity relative to CHX and did not induce drug resistance in S. mutans after 15 passages. Conclusion : - II-6s may serve as a promising part of a successful caries management plan.